1992
DOI: 10.1161/01.atv.12.11.1305
|View full text |Cite
|
Sign up to set email alerts
|

Long-term nicotine exposure increases aortic endothelial cell death and enhances transendothelial macromolecular transport in rats.

Abstract: Repeated endothelial cell injury has been suggested as an initiating factor in atherogenesis. Dying or dead endothelial cells have been shown to make significant contributions to the local enhancement of transendothelial macromolecular transport. Since cigarette smoking is one of the major risk factors for atherosclerosis, we examined the hypothesis that smoking accelerates atherogenesis by increasing the frequency of endothelial cell death and hence transendothelial macromolecular transport. Sixteen male Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
3
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 39 publications
3
31
3
2
Order By: Relevance
“…The association between smoking and elevated TER alb in our NIDDM patients has also been demonstrated in non-diabetic subjects [52]. Several factors may contribute such as carbon monoxide [53], nicotine [54], and acute intermittent blood pressure elevation in association with smoking [55].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The association between smoking and elevated TER alb in our NIDDM patients has also been demonstrated in non-diabetic subjects [52]. Several factors may contribute such as carbon monoxide [53], nicotine [54], and acute intermittent blood pressure elevation in association with smoking [55].…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, repeated endothelial cell injury and increased lipid entry have been suggested as initiating events in atherogenesis [60]. Animal studies have demonstrated increased aortic endothelial cell death and enhanced transendothelial macromolecular transport in experimental diabetes, hypertension, and during nicotine consumption [54,61,62]. Diabetes, hypertension, cigarette smoking are well-known risk factors for macroangiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Yet In our unpublished studies, 24 h treatment of EA.hy926 cells with 25% and 50% CSE prepared from burning three cigarettes per 10 ml culture medium induced mostly early apoptosis (unpublished data). An in vivo increase in cell death frequency was observed by Lin et al following treatment of rats with nicotine [33].…”
Section: Discussionmentioning
confidence: 76%
“…[33][34][35] In this study, the lack of evidence for apoptosis in either the smoking animals or the nonsmoking controls demonstrated that programmed cell death is not a normal part of the early healing response in the mouse MCL and that increased apoptosis was not responsible for the decreased cell density in the injured ligament of mice exposed to cigarette smoke.…”
Section: Discussionmentioning
confidence: 95%